Interpersonal violence-related physical injury in low- and middle-income countries and its association with markers of socioeconomic status: a systematic review - Kevin J. Blair; Haley Tupper; Jordan M. Rook; Michael de Virgilio; Thiago S. Torres; Akshayaa K. Chittibabu; M. Wynn Tranfield; Bethany Myers; Alan Hubbard; Alain Chichom-Mefire; Mary-Margaret Ajiko; Catherine Juillard; et al. (BMC Public Health)
Abstract Background Interpersonal violence-related physical injury (IPVRPI) is a leading cause of death in low- and middle-income countries (LMICs), yet reliable data relating socioeconomic status (SES) and IPVRPI in these settings are lacking. We analyzed existing literature on associations between SES and IPVRPI in LMICs to understand how SES is measured in these contexts and synthesize data relating markers of SES to IPVRPI at the individual-level in order to inform future hospital-based IPVRPI prevention efforts. Methods We searched Ovid MEDLINE, EMBASE, and Global Health databases in January 2022 for analytical studies from LMICs that explored individual-level associations between IPVRPI and markers of SES. Studies about intimate partner violence, suicide, or children < 12 years old were excluded, as were population-level studies. Markers of SES considered were educational attainment, employment, and household wealth. Collated data relating these SES indicators with IPVRPI were presented in forest plots. Results A total of 34 studies from 20 LMICs were included. Brazil, Mexico, and South Africa were the most represented countries. Studies were mostly cross-sectional (n = 23), and data were typically from patient hospital records (n = 17) or population surveys (n = 12). Included studies explored associations between IPVRPI and education (n = 26), employment (n = 26), and household wealth (n = 19). Categorizations, particularly for employment and wealth, were highly variable between studies. Among the studies that performed multivariable analyses, IPVRPI was found to be significantly associated with lower educational attainment (n = 6), unemployment (n = 4), and lower household wealth (n = 6). Conclusions Numerous studies have explored individual-level associations between IPVRPI and markers of SES among LMIC populations. Across a variety of LMIC contexts, we found that IPVRPI tended to be associated with markers of lower SES. Further conclusions were limited by the heterogeneity of SES measure categorizations, varied IPVRPI case definitions, and lack of adjusted analyses. Future research should ensure SES measures utilized in LMICs are comprehensive and comparable, focus more specifically on IPVRPI from community violence, and consider hospital-based interventions to reduce risk of IPVRPI in LMIC settings.